33.1k views
3 votes
Integrate
e^(4x)\sqrt{1+e^(2x) } dx please show work so i can learn

User Alan Omar
by
4.4k points

1 Answer

3 votes

Answer:


(\frac{(1+e^(2x)) ^{(5)/(2) } }{{5}} + \frac{(1+e^(2x) )^{(3)/(2) } }{{3}} )+C

Explanation:

Step(i):-

Given that the function

f(x) =
e^(4x) \sqrt{1+e^(2x) }

Now integrating on both sides, we get


\int\limits{f(x)} \, dx = \int\limits{e^(4x) \sqrt{1+e^(2x) } dx

=
\int\limits{e^(2x) e^(2x) \sqrt{1+e^(2x) } dx

Step(ii):-

Let
1 + e^(2x) = t


e^(2x) = t -1


2e^(2x)dx = d t


e^(2x)dx = (1)/(2) d t

=
\int\limits{( \sqrt{1+e^(2x) }) e^(2x) e^(2x) dx

=
\int\limits {√(t)(t-1)(1)/(2) dt }

=
(1)/(2) \int\limits {√(t) (t) -√(t) ) dt }

=
(1)/(2) \int\limits {(t^{(1)/(2) } t^(1) +t^{(1)/(2) } ) } \, dx


= (1)/(2) \int\limits {(t^{(3)/(2) } +t^{(1)/(2) } ) } \, dx

=
(1)/(2) (\frac{t^{(3)/(2) +1} }{(3)/(2)+1 } + \frac{t^{(1)/(2) +1} }{(1)/(2)+1 } )+C

=
(1)/(2) (\frac{t^{(3)/(2) +1} }{(5)/(2) } + \frac{t^{(1)/(2) +1} }{(3)/(2) } )+C

=
(1)/(2) (\frac{t^{(5)/(2) } }{(5)/(2) } + \frac{t^{(3)/(2) } }{(3)/(2) } )+C

=
(\frac{(1+e^(2x)) ^{(5)/(2) } }{{5}} + \frac{(1+e^(2x) )^{(3)/(2) } }{{3}} )+C

Final answer:-

=
(\frac{(1+e^(2x)) ^{(5)/(2) } }{{5}} + \frac{(1+e^(2x) )^{(3)/(2) } }{{3}} )+C

User Mrzool
by
5.3k points